Modeling and simulation of SEPIC controlled converter using PID controller - Salam Ibrahim Khather; Muhammed A. Ibrahim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The topology of SEPIC "Single-ended primary inductance converter" is considered as a suitable option for automotive power system where the value of the output voltage should be ranging between the low and high values of the input value of voltage. The main feature of the DC-DC converter is the stability of output voltage. This paper shows the SEPIC converter employing PID converter to be used in industrial applications. A SEPIC DC-DC converter can manage either step-down mode or step-up mode. The benefit of using this circuit is to supply a stable and controlled output voltage no matter how much the input voltage is. The simulated behaviors of the uncontrolled and controlled SEPIC converter are presented in this paper. The PID controller based on bat algorithm (BA) optimization method is used for searching of the best Proportional–Integral-Derivative (PID) gains. The solution has given very good performance and whatever the output reference voltage variation and load disturbance of the system.